Genetic Diversity of Groundnut (Arachis hypogaea L.) Revealed by RAPD and ISSR Markers - Reddy, Papi; Sabara, Pritesh; Padhiyar, Shital M.; Kulkarni, G.U.; Kheni, J.V.; Tomar, Rukam S. (Annals of Arid Zone, 2022)
The genetic diversity of twenty-six genotypes of groundnut was evaluated using RAPD (Random amplified polymorphic DNA) and ISSR (Inter-simple sequence repeat) markers. Fifteen RAPD primers produced 58 bands out of which 44 were polymorphic. The average percentage of polymorphism and the polymorphic information content (PIC) for RAPD was calculated as 73.11 and 0.691, respectively while Jaccard’s similarity percentage ranged between 63.0-97.0. Thirty-one ISSR primers amplified 98 polymorphic bands out of total 146 bands obtained. In ISSR analysis, average values for fragments per primer, percentage of polymorphism and PIC were 89.87, 65.05 and 0.728, respectively. Jaccard’s similarity percentage range for ISSR data was from 66.0-93.0.